2005
DOI: 10.1016/j.ultsonch.2004.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ultrasonic degradation of phenol in the presence of TiO2 particles

Abstract: The degradation of phenol by ultrasonic irradiation in the presence of TiO2 was investigated in complete darkness. The effects of amount of TiO2 and the combination of TiO2 addition with gas (air or oxygen) supply on the degradation kinetics of phenol and the formation of the reaction products were examined. The degradation rate of phenol increased with the amount of TiO2. As the dissolved oxygen concentration increased by supplying oxygen, the degradation rate of phenol also increased. A kinetic model for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…These experiments have also shown that lower pH, high concentration of dissolved O 2 and ultrasonic power density also enhanced the phenol degradation. Kubo et al [82] examined the ultrasonically induced phenol degradation with TiO 2 in complete dark and found the phenol degradation rate to be higher in the presence the TiO 2 compared to that of sonication alone. The rate also enhanced linearly with the catalyst amount.…”
Section: Sonochemical Methodsmentioning
confidence: 99%
“…These experiments have also shown that lower pH, high concentration of dissolved O 2 and ultrasonic power density also enhanced the phenol degradation. Kubo et al [82] examined the ultrasonically induced phenol degradation with TiO 2 in complete dark and found the phenol degradation rate to be higher in the presence the TiO 2 compared to that of sonication alone. The rate also enhanced linearly with the catalyst amount.…”
Section: Sonochemical Methodsmentioning
confidence: 99%
“…Kubo et al have been investigated the effects of TiO 2 particles addition on degradation of phenol [19]. The reaction rate of phenol was enhanced by TiO 2 particle addition and degradation was a pseudo-first-order reaction.…”
Section: Effect Of Particle Addition On Apparent Degradation Rate Conmentioning
confidence: 99%
“…Especially, the combination of photocatalysis and ultrasound is considered to enhance the degradation rate [4] [5]. The degradation of phenol by ultrasonic irradiation in the presence of TiO 2 particles has been investigated in complete darkness [19]. Sekiguchi and Saita have investigated the effect of Al 2 O 3 particles on the degradation of chlorobenzene in an ultrasonic field [20].…”
Section: Introductionmentioning
confidence: 99%
“…21 All these researches have made possible an invaluable understanding of cavitation and its promotion of the efficiency of hybrid technologies. 22,23 Recently, Zhao et al 17 found that ultrasound enhances electrochemical oxidation of phenol on boron-doped diamond and Pt electrodes. The enhancement by ultrasound depends on the electrode material, being much greater on boron-doped diamond than on Pt.…”
Section: Electrochemical Versus Sonoelectrochemicalmentioning
confidence: 99%